Zarządzanie wiedzą zorientowane na procesy biznesowe : podstawowe założenia - Tabaszewska, Edyta (Process-Oriented Knowledge Management : Basic Foundations, 2009)
The aim of the article is to present the idea of process-oriented knowledge management (PKM), its basic features and advantages of its applying. PKM is designed to provide employees with task-related knowledge during the process enactment phase. Both knowledge management and process management are more efficient.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 117-126